PERBAIKAN MESIN PENGERING DAUN AFRIKA DI SMKN 1 WONOSARI KABUPATEN MALANG MENGGUNAKAN METODE REVERSE ENGINEERING - D. H. Praswanto; Siswi Astuti; Endah Kusuma Rastini; Fourry Handoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi Nasional Malang, 2021)
Sumberdem Village in Wonosari Subdistrict, Malang Regency, has agricultural products in the form of medicinal plants, one example is African leaves. This plant is used as a tea product for consumption by diabetics. SMKN 1 Wonosari is a partner that produces African leaf tea. To make African leaf tea products, use a dryer. The drying machine owned by SMKN 1 Wonosari was not optimal due to several problems when we used it. There were 3 problems when the team used the partner's dryer, namely the location of the heating element was not optimal so that the drying of the African leaves was not evenly distributed, the sharp edges of the racks could cause work accidents and the wheels on the drying mat were not strong enough to withstand the load. The solution to the problem used is repairing the dryer. There are 3 methods in community service activities carried out to achieve the outcome, namely the approach method, the reverse engineering method and on the job training. The result of this activity is an African leaf drying machine using a heating element on each shelf. This drying machine with 1450 watts of power has the advantage that the results of drying African leaves can be evenly distributed, drying time is faster and safer to use. The use of this drying machine partners can save production costs of Rp. 7,403 for every 4kg of wet African leaves.